Weightlifting overhead pressing derivatives: A review of the literature - Soriano, M. A.; Suchomel, T. J.; Comfort, P. (Sports Medicine, 2019)
This review examines the literature on weightlifting overhead pressing derivatives (WOPDs) and provides information regard-ing historical, technical, kinetic and kinematic mechanisms as well as potential benefits and guidelines to implement the use of WOPDs as training tools for sports populations. Only 13 articles were found in a search of electronic databases, which was employed to gather empirical evidence to provide an insight into the kinetic and kinematic mechanisms underpinning WOPDs. Practitioners may implement WOPDs such as push press, push jerk or split jerk from the back as well as the front rack position to provide an adequate stimulus to improve not only weightlifting performance but also sports performance as: (1) the use of WOPDs is an additional strategy to improve weightlifting performance; (2) WOPDs require the ability to develop high forces rapidly by an impulsive triple extension of the hips, knees and ankles, which is mechanically similar to many sporting tasks; (3) WOPDs may be beneficial for enhancing power development and maximal strength in the sport population; and, finally, (4) WOPDs may provide a variation in training stimulus for the sports population due to the technical demands, need for balance and coordination. The potential benefits highlighted in the literature provide a justification for the implementation of WOPDs in sports training. However, there is a lack of information regarding the longitudinal training effects that may result from implementing WOPDs. Abstract from author